Incidental Learning as an Enacted Encounter with Materiality. Issue 159 (17th September 2018) - Justice, Sean; Yorks, Lyle
Abstract: This chapter adopts an enactivist framework to analyze the incidental and informal learning of a middle‐school teacher.